2013
DOI: 10.1186/1472-6882-13-295
|View full text |Cite
|
Sign up to set email alerts
|

The co-use of conventional drugs and herbs among patients in Norwegian general practice: a cross-sectional study

Abstract: BackgroundDifferent patient groups are known to use herbal remedies and conventional drugs concomitantly (co-use). This poses a potential risk of herb-drug interaction through altering the drug’s pharmacokinetics or pharmacodynamics. Little is known about co-use among patients in general practice. The primary aim of this study was to compare patients in general practice that co-use herbal remedies and conventional drugs with those who do not. The secondary aim was to register the herb-drug combinations with po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
91
2
12

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(114 citation statements)
references
References 48 publications
9
91
2
12
Order By: Relevance
“…Similarly, another study reported that physicians seldom ask if the patient was using herbal therapies [55]. Therefore, many patients end up using herbal and conventional therapies concurrently [12]. This has been attributed to poor communication and the insufficient time allocated to the clinical consultation [56].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, another study reported that physicians seldom ask if the patient was using herbal therapies [55]. Therefore, many patients end up using herbal and conventional therapies concurrently [12]. This has been attributed to poor communication and the insufficient time allocated to the clinical consultation [56].…”
Section: Discussionmentioning
confidence: 99%
“…The potential harms and benefits provided by the interviewed gynecologists and women were noted. We then conducted an extensive literature review to identify potential harms and benefits of using ginger in pregnant women [13, 68, 11, 12, 18–35]. All potential harms and benefits provided by the gynecologists and women as well as those found in the literature were summarized, formulated into statements, and included into a questionnaire.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…I følge Bransjerådet for naturmidler bruker vi i Norge naturmidler og kosttilskudd for mer enn 2 milliarder kroner i året (3). Trass i at behandling med naturmidler er utbredt (4), kan informasjon om pasientenes inntak av slike midler vaere mangelfull (5). Naturmidlene kan -avhengig av innhold -betraktes som enten kosttilskudd eller legemidler, og import av begge disse produktkategoriene er omfattet av restriksjoner (6).…”
Section: Diskusjonunclassified
“…This has significant implications particularly in preor post-operative patients, patients with clotting disorders, those on anticoagulant therapy, and the elderly [35]. Elderly patients pose significant risk due to polypharmacy and polyherbacy issues [36,37].…”
Section: The Importance Of Cam In Australian Clinical Practicementioning
confidence: 99%